(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research is motivated by the learning osbtacles findings regarding algebraic thinking caused by students have not received formal algebra learning in elementary school. On the other hand, previous research states that algebraic thinking can be accustomed since elementary school age. This habituation can be done by choosing elementary school mathematics material that has the potential to be used as a learning precondition for algebra or called algebraic thinking. Thus the need for a learning plan that can improve the algebraic thinking ability of elementary school student. This research uses the Didactical Design Research (DDR) research method. The stages of this research method consisted of prospective analysis, methadactic analysis and retrospective analysis. After an analysis of learning obstacles is carried out, field findings are triangulated into learning trajectories. The process of analysis and triangulation produces alternative didactic situations that can overcome obstacles in algebra thinking. The alternative didactic situation is used as the basis for developing lesson designs that will be implemented. This research produced lesson design in algebra thinking class V in elementary school. Based on field studies that think algebra in the curriculum in primary schools is not explicitly stated, it is necessary to develop lesson design to facilitate students in developing algebraic thinking.